ANCA: A Web Server for Amino Acid Networks Construction and Analysis - Yan, Wenying; Yu, Chunjiang; Chen, Jiajia; Zhou, Jianhong; Shen, Bairong (Frontiers in Molecular Biosciences, 2020)
Amino acids network (AAN) models empower us to gain insights into protein structures and functions by describing a protein 3D structure as a graph, where nodes represent residues and edges as amino acids interactions. Here we present the ANCA, an interactive web-server for Amino Acids Network Construction and Analysis based on single structure or a set of structures from the Protein Data Bank. The main purpose of ANCA is to provide a portal for three types of evironment-dependent contact energy (ERCE) based network model, including amino acids contact energy networks (AACEN), node-weighted amino acids contact energy networks (NACEN), edge-weighted amino acids contact energy networks (EACEN). For comparison, the C-alpha distance based network model is also included, which can be extended to protein-DNA/RNA complexes. Then, the analysis of different types of AANs were performed and compared from node, edge and network levels. The network and corresponding structure can be visualized directly in the browser. The ANCA enables researchers to investigate diverse concerns in the framework of AAN, such as the interpretation of allosteric regulation and functional residues. The ANCA portal, together with an extensive help, is available at http://sysbio.suda.edu.cn/anca/.